2011
DOI: 10.1038/nm.2597
|View full text |Cite
|
Sign up to set email alerts
|

Recipient nonhematopoietic antigen-presenting cells are sufficient to induce lethal acute graft-versus-host disease

Abstract: The presentation pathways by which allogeneic peptides induce graft-versus-host disease (GVHD) are unclear. We developed a bone marrow transplant (BMT) system in mice whereby presentation of a processed recipient peptide within major histocompatibility complex (MHC) class II molecules could be spatially and temporally quantified. Whereas donor antigen presenting cells (APCs) could induce lethal acute GVHD via MHC class II, recipient APCs were 100-1,000 times more potent in this regard. After myeloablative irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
212
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(230 citation statements)
references
References 41 publications
16
212
0
2
Order By: Relevance
“…Important evidence for this is provided by the experiments performed in which donor DCs can present indirect Ag but do not bear cross-dressed Ag, a situation in which significantly lower levels of proliferation are seen compared with intact DC capable of using both pathways. Prior studies within our group (2,6) have demonstrated that classical indirect MHC II presentation pathways are inefficient at inducing GVHD in isolation and indeed become defective during GVHD. Thus, in the setting of GVHD, in which MHC II presentation of processed peptide is impaired, the role for MHC present owing to the phenomenon of cross-dressing may become even more important for enabling an effective T cell response.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Important evidence for this is provided by the experiments performed in which donor DCs can present indirect Ag but do not bear cross-dressed Ag, a situation in which significantly lower levels of proliferation are seen compared with intact DC capable of using both pathways. Prior studies within our group (2,6) have demonstrated that classical indirect MHC II presentation pathways are inefficient at inducing GVHD in isolation and indeed become defective during GVHD. Thus, in the setting of GVHD, in which MHC II presentation of processed peptide is impaired, the role for MHC present owing to the phenomenon of cross-dressing may become even more important for enabling an effective T cell response.…”
Section: Discussionmentioning
confidence: 95%
“…GVHD remains one of the key complications of BMT as therapy for hematological malignancy, and despite advances in the field, further insights into disease pathogenesis remain important for design of therapeutic strategies. Donor alloreactive T cells may be stimulated by direct interaction with host-type MHC from either hematopoietic or nonhematopoietic sources (2,3) or by donor cells presenting processed, acquired Ag via the indirect pathway (2,(4)(5)(6). In addition to these two classical pathways, we have been interested in the semidirect pathway of Ag presentation, whereby a donor APC which has acquired MHC of host-type, via "trogocytosis" or "cross-dressing" could potentially stimulate antihost responses from donor T cells (7)(8)(9).…”
mentioning
confidence: 99%
“…[2][3][4] Experimental and clinical data support the hypothesis that immune dysregulation during GVHD occurs in distinct phases 3 involving diffuse damage and inflammation from conditioning regimens, activation of donor T cells by host-derived antigen-presenting cells, [5][6][7] and target organ injury by soluble and cellular effectors. Since its inception, components of this paradigm have been challenged and refined.…”
Section: Introductionmentioning
confidence: 88%
“…GVHD is initiated by the presentation of recipient alloantigens, predominantly by host APCs to donor T cells (1,2). The subsequent differentiation and expansion of effector CD4 and CD8 T cells result in a complex proinflammatory cascade in which apoptosis is induced in target organs by both cytokines (especially TNF, IFN-g, and IL-6) and cellmediated cytotoxicity (3)(4)(5)(6).…”
mentioning
confidence: 99%